The European structure of digital competences in Ukrainian society: challenges and innovations - Batyuk, Liliya (Journal of Education, Health and Sport, 2017)
Digital competences in education not only improve the learning process, but also stimulate changes in the pedagogical process on the path of informatization of Ukrainian education and society as a whole and directly affect the reduction of the «digital divide». In recent years, the position of information and communication technologies (ICT) in Ukrainian society and education has strengthened. In addition to ICT infrastructure, digital content creation and teacher training initiatives, recent curriculum reforms support the use of digital technologies in many subjects. In order for citizens to improve their digital competence, the European Commission has proposed a tool known as The European Digital Competence Framework (DigComp). In this article, we analyze a number of concepts and approaches related to the European structure of digital competences in Ukrainian society and related with it the projects and initiatives of the Ministry of Education and Science of Ukraine on several educational, cultural and disciplinary grounds.